Rural and cultural tourism development focusing on community-based tourism (CBT): the case of Qwaqwa - Mohlakoana, Tlhoriso L. (University of the Free State, 2024)
Rural communities have been finding it more difficult to sustain themselves in recent years due to the migration of large numbers to urban areas searching for more promising livelihoods. Rural areas face many challenges, including unemployment, poverty, lack of services, and other social ills. The unique culture and natural environment of rural areas can be explored through Community-Based Tourism (CBT). The South African government deems tourism as one of the vehicles that can be positively used to uplift rural communities and address the identified challenges these communities face. CBT dictates that the community’s own tourism products found in their area should be involved in tourism development, subsequently deriving the most benefits from tourism initiatives. This study aimed to investigate whether CBT with a cultural emphasis can be used to uplift the rural communities of Qwaqwa in the Eastern Free State. This, firstly, required investigating the best practices to be used by rural communities for their socio-economic development. Secondly, it was necessary to determine the impacts of exposing rural cultures and natural environments to attract economic activity. Thirdly, it was necessary to explore guidelines on how to sustain CBT initiatives. Lastly, an investigation into the roles of different stakeholders in ensuring the sustainability of CBT projects had to be conducted. This study was qualitative in nature and used interview schedules to collect data from households and tourism businesses in Qwaqwa. After the data analysis, it became apparent that the study area did not have many CBT businesses, with many existing businesses requiring significant support. It further became evident that few community members are involved in tourism, subsequently not benefiting from it. As a result, it was recommended that the government, through its different agencies, educate and assist communities with the development of CBT projects.
Dissertation(MDS (Development Studies))--University of the Free State, 2025
Keywords: Community-based tourism; Rural tourism; Cultural tourism; Tourism development; Tourism initiative